Experience of Asian Asset Management Companies: Do They Increase Moral Hazard? Evidence from Thailand - Akiko Terada-Hagiwara; Gloria Pasadilla (Asian Development Bank (ADB), 2004)
"This paper examines the performance of Asian asset management companies (AMCs). The analysis reveals that the AMCs vary in their design and performance. The paper claims that AMCs can trigger moral hazard-induced bank lending. Empirical examination of the Thai experience of AMCs reveals that moral-hazard induced bank lending resulted in creating more new nonperforming loans (NPL) in the case of public AMCs. On the other hand, the centralized Thai Asset Management Company decreases the new NPL ratio, suggesting that this centralized AMC provokes no adverse moral hazard effect on financial institutions."
hdl:11540/1914
Keywords: 330; Finanzdienstleistung; Vermögensverwaltung; Kreditgeschäft; Moral Hazard; Thailand